ST-32AB : optimal sensor placement for response prediction of civil engineering structures subjected to future uncertain dynamic loadings - Phua, Tarius Xing Jian (2014)
Engineers often encounter difficulties identifying the model parameters for a structural model with dynamic data. The limitations and problems are due to insufficient excitation, uncertainties in the mathematical models used in the parameters simulation and also inadequate response of bandwidth.